Aprendizaje cooperativo para fortalecer Lengua y Literatura en el quinto grado de Educación General Básica - Guevara Cango, Rosa Maribel (2025)
The research on cooperative learning to strengthen Language and Literature in the fifth grade of Basic General Education; has as general objective; to determine the incidence of cooperative learning in the strengthening of Language and Literature in the fifth grade of Basic General Education; it is a descriptive type research, with a mixed approach and nonexperimental design; the theoretical framework addresses the topics: cooperative learning and learning of Language and Literature, in the investigative process the following methods were used: scientific, descriptive, analytical, synthetic and statistical; the collection of information was carried out through the application of a diagnostic evaluation and a structured interview with the teacher, the research population includes twenty-two students and one teacher; The results of the diagnosis indicate that a high percentage of the investigated students are close to achieving the required learning and a considerable percentage achieves the required learning, this suggests the need to carry out actions that allow strengthening the learning of this important subject, for this, the guideline "Learning together the magic of Language and Literature" is designed based on cooperative learning whose execution will contribute significantly to the integral development of the students, since it gives them the opportunity to enrich their knowledge through active interaction with their peers. Keywords: cooperative learning, Language and Literature, teaching, strategies